PENGARUH PROFITABILITAS, LIKUIDITAS, SOLVABILITAS, DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN (STUDI KASUS PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR FOOD AND BEVERAGE YANG TERDAFTAR DI BEI PERIODE 2021-2023) - Shintya Aprilia Utami; Khasanah Sahara; Ninik Anggraini; Srikalimah (Cahaya Ilmu Bangsa, 2025)
This research aims to test and analyze how profitability is influenced by proxies LONG And ROE, liquidity by proxy CR And QR, solvency by proxy THE And LTDER, and dividend policy by proxy DPR And YOU on Company Value. This research is descriptive research with quantitative methods. The sampling technique in this research is purposive sampling with a population of 30 sub-sector manufacturing companies food and beverage and obtained a sample of 8 companies food and beverage. The data analysis technique used is the classic assumption test which consists of the normality test, multicollinearity test, heteroscedasticity test, and auto correlation test, hypothesis test which consists of the R2 coefficient of determination test, t test, and f test, as well as the multiple linear regression test. The results of this research state that profitability through LONG influence on company value with a sig value of 0.002 <0.05, profitability through ROE has no effect on company value with a sig value of 0.666 > 0.05, liquidity through CR influence on company value with a sig value of 0.058 <0.05, liquidity through QR has no effect on company value with a sig value of 0.341 > 0.05, solvency through THE has no effect on company value with a sig value of 0.988 > 0.05, solvency through LTDER has no effect on company value with a sig value of 0.486 > 0.05, dividend policy through DPR has no effect on company value with a sig value of 0.498 > 0.05, dividend policy through YOU has no effect on company value with a sig value of 0.816 > 0.05. Meanwhile, simultaneously ROA, ROE, CR, QR, DER, LTDER, DPR, And YOU influence on PBV.